The Impact of Awarding Incentives on Posyandu Cadre Performance - Atik Farokah; Qatrunnada Naqiyyah Khusmitha; Herdian Fitria Widyanto Putri; Eri Kurniasari (Jurnal Kedokteran Diponegoro, 2023)
Background:Stunting is a condition of failure to thrive due to chronic malnutrition that occurs in toddlers. Posyandu is an intervention facility for a specific nutrition program carried out by the Ministry of Health. The role of posyandu cadres is very important in efforts to reduce the prevalence of stunting. The Government of Malang Regency implements a cash incentive program for all posyandu cadres to improve their performance.